How far perceived quality and satisfaction are important for customer brand loyalty? The case of the portuguese mobile market - Faria, Sílvia (2022)
This paper aims to analyze the importance of quality and customer satisfaction in the Portuguese mobile market as variables leading to customer loyalty. Several attitudinal and behavioral drivers of brand loyalty were examined, as well as the possible relationship between them and how they impact in lasting relationships between consumers and mobile brands. Previous literature supported the development of a set of hypotheses. The model was tested on an empirical study based on a survey to 231 Portuguese consumers, with questions measuring the main concepts (brand loyalty, trust, involvement/engagement, satisfaction and quality). Statistical analysis included descriptive statistics (means, standard deviation, Cronbach’s alpha), paired-samples T-test, data reduction techniques and hierarchical regression analysis. Results reveal that repurchase intention, as a proxy to brand loyalty, is influenced by all the considered concepts. However, brand trust and brand involvement impact on brand commitment and seem to be stronger predictors of brand loyalty. Since this article considered brand loyalty as the sum of repurchase intention and brand commitment, expected quality is not relevant for neither of them. Trust seems to impact on brand commitment but not in repurchase intention. Performed Quality is statistically significant but through consumer satisfaction. Therefore, Satisfaction and Involvement/Engagement lead to strong brand commitment and repurchase intention and performed quality is also an independent variable that leads customers to brand loyalty in the mobile market. Results are discussed in light of the consumer-brand relationship theory. Despite some limitations (our study is only limited to Portugal, to a sample of young consumers mainly from the north of the country), this study offers a reasoned view on consumer-brand relationship. Aiming to identify the role of quality and customer satisfaction in the Portuguese telecommunication market, we hypothesized customer satisfaction as a mediator to involvement/engagement, trust and brand loyalty. To keep customers’ attention and achieve brand loyalty (commitment + repurchase intention), any Portuguese telecommunication player needs to satisfy clients by betting on perceived quality in time and to involve them, offering accurate information on products and services. If so, consumers will feel satisfied, trust and develop a strong feeling towards the brand.